Efficacy and safety of tacrolimus compared with ciclosporin‐A in renal transplantation: 7‐year observational results. (11th December 2015) - Krämer, Bernhard K.; Montagnino, Giuseppe; Krüger, Bernd; Margreiter, Raimund; Olbricht, Christoph J.; Marcen, Roberto; Sester, Urban; Kunzendorf, Ulrich; Dietl, Karl‐Heinz; Rigotti, Paolo; Ronco, Claudio; Hörsch, Silke; et al.
Summary: The European Tacrolimus versus Ciclosporin‐A Microemulsion (CsA‐ME) Renal Transplantation Study demonstrated that tacrolimus decreased acute rejection rates at 6 months. Primary endpoints of this investigator‐initiated, observational 7‐year follow‐up study were acute rejection rates, patient and graft survival rates, and a composite endpoint (BPAR, graft loss, and patient death). We analyzed data from the original intent‐to‐treat population ( n = 557; 286 tacrolimus, 271 CsA‐ME). A total of 237 tacrolimus and 208 CsA‐ME patients provided data. At 7 years, Kaplan–Meier estimated rates of patients free from BPAR were 77.1% in the tacrolimus arm and 59.9% in the CsA‐ME arm, graft survival rates amounted to 82.6% and 80.6%, and patient survival rates to 89.9% and 88.1%. Estimated combined endpoint‐free survival rates were 60.2% in the tacrolimus arm and 47.0% in the CsA‐ME arm ( P = <0.0001). A higher number of patients from the CsA‐ME arm crossed over to tacrolimus during 7 year follow‐up: 19.7% vs. 7.9% ( P = <0.002). More patients in the tacrolimus group stopped steroids and received immunosuppressive monotherapy. Significantly, more CsA‐ME patients received lipid‐lowering medication and experienced cosmetic and cardiovascular adverse events. Tacrolimus‐treated renal transplant recipients had significantly higher combined endpoint‐free survival rates mainly driven by lower acute rejection rates despite less immunosuppressive medication at 7 years.